Redesigning Public Street Lighting Using Photometric Method - Ade Gafar Abdullah; Muhammad Aziz; Muhammad Nur Huda (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2021)
Street lighting with LED (Light-Emitting Diode) technology is currently the main option of public lighting in almost every country. Even though LED technology is a less costly selection, there needs to be well planned in an attempt of acquiring high efficiency. The photometric approach was tested in this study in order to redesign the existing approach used in street lighting in Indonesia. The redesigning process was carried out using software namely DIALux on two different schemes; one with homogeneous luminaire and the other one with the non-homogeneous luminaire. The results of this study showed that the most significant factors in redesigning street lighting covered types of the lamp, pole distance, pole height, and proper lighting angles which could affect the illumination value on both the main road and the sidewalks. In addition, it has also been proven that a homogeneous approach using LED lamp lighting promoted uniformity as well as optimum illumination.